Cultural localization in online heritage promotion. Issue 3 (4th May 2021) - Mele, Emanuele; Kerkhof, Peter; Cantoni, Lorenzo
ABSTRACT: This research examines the effects of localizing cultural values on perceived image and willingness to visit a heritage site. Using Collectivism-Individualism and Power Distance, two preregistered experiments were conducted with a total of 2039 respondents from Portugal and United Kingdom. In Study 1, against expectations, culturally incongruent webpage content expressing low (vs. high) Power Distance generates a higher willingness to visit among Portuguese participants. In Study 2, localized webpage content expressing Individualism (vs. Collectivism) leads to a higher willingness to visit among UK respondents, with the mediation of perceived image. Neither experiment shows an effect of the stimuli on perceived image. Findings suggest limited benefits of localization for heritage promotion and a high tolerance of participants toward incongruent cultural values.